2021
DOI: 10.3390/pharmaceutics13020290
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Inflammatory Mediators by Polymeric Nanoparticles Loaded with Anti-Inflammatory Drugs

Abstract: The first-line treatment of osteoarthritis is based on anti-inflammatory drugs, the most currently used being nonsteroidal anti-inflammatory drugs, selective cyclooxygenase 2 (COX-2) inhibitors and corticoids. Most of them present cytotoxicity and low bioavailability in physiological conditions, making necessary the administration of high drug concentrations causing several side effects. The goal of this work was to encapsulate three hydrophobic anti-inflammatory drugs of different natures (celecoxib, tenoxica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 68 publications
0
11
0
Order By: Relevance
“…Various studies have reported on polymeric NPs as drug delivery systems for different classes of drugs to enhance their solubility, efficacy and bioavailability. [54][55][56][57][58] In this study, we developed an NP formulation for ROF, a promising bioactive flavonoid, based on PLGA. PLGA-based polymeric NPs have been previously employed to enhance the bioavailability, biological activity, and water solubility of various natural products.…”
Section: Discussionmentioning
confidence: 99%
“…Various studies have reported on polymeric NPs as drug delivery systems for different classes of drugs to enhance their solubility, efficacy and bioavailability. [54][55][56][57][58] In this study, we developed an NP formulation for ROF, a promising bioactive flavonoid, based on PLGA. PLGA-based polymeric NPs have been previously employed to enhance the bioavailability, biological activity, and water solubility of various natural products.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, DEX has been shown to act as a non-specific immune inhibitor (42). It was reported that its use inhibited the production of numerous inflammatory mediators and increased the synthesis of proteins associated with anti-inflammatory responses (43). Its use for therapeutic intervention has been reported in SAP-associated ALI (44).…”
Section: Discussionmentioning
confidence: 99%
“…However, this technique has some disadvantages, including large operative trauma and economic burden for the individuals affected. The conventional strategy before surgery is the use of corticosteroids such as dexamethasone (Dex), which can alleviate inflammation and reduce the degradation of the chondrocyte extracellular matrix, but corticosteroids can not reverse the progression of OA. , Kartogenin (KGN) can promote the chondrogenic differentiation of stem cells by regulating the CBFβ-RUNX1 pathway and prevent the degeneration of OA-induced cartilage and subchondral bone. , Notably, the low water solubility and fast removal of these drugs result in poor intra-articular delivery efficiency . Consequently, the design and optimization of an intra-articular dual-drug delivery system can provide a meaningful strategy to mitigate the inflammatory response and promote chondrocyte differentiation in OA therapy.…”
Section: Introductionmentioning
confidence: 99%